PENGARUH MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT BER-ENTREPRENEUR - Novita Erliana Sari; Novi Triana Habsari (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
The purpose of this study was to determine the extent of implementation of entrepreneurship courses have a positive impact on the interest in entrepreneurship. The population in this study were all students who have exhausted FPIPS entrepreneurship courses. The sample in this study amounted to 50 respondents. Methods of data analysis using multiple linear regression with the help spss.16 for windows. Based on the analysis of data obtained by the regression equation Y = 7.121 + 0.421 x1 + 0,600 x2 + e. This shows that both the dependent variable, the variable application will provide the greatest impact to variable interest in air-entrepreneurs, it is because by implementing entrepreneurship courses, indirectly, students can foster interest in air-entrepreneur. Conclusions can be drawn from this study that: the implementation of entrepreneurship courses are explained by understanding the variable (X1) and application (X2) proved a significant effect on student interest variable air-entrepreneur (Y). This is because the understanding of the subjects of entrepreneurship trigger students to apply so as to foster interest among students air-entrepreneur FPIPS IKIP PGRI Madiun.